Viability Improvement of Three‐Dimensional Human Skin Substitutes by Photobiomodulation during Cultivation. (17th May 2022) - Tsunoi, Yasuyuki; Miyazaki, Hiromi; Kawauchi, Satoko; Akagi, Takami; Akashi, Mitsuru; Saitoh, Daizoh; Sato, Shunichi
Abstract: Three‐dimensional (3D) cultured skin containing vascular networks is a useful skin substitute that enables rapid reperfusion after transplantation. During its cultivation, however, insufficient nutrient delivery to the thick cultured tissue from the surrounding culture medium decreases the tissue viability. To solve this problem, in this study, we applied photobiomodulation (PBM), which can optically activate the electron transport chain of mitochondria, to human 3D skin cultures constructed using the layer‐by‐layer cell coating technique. PBM was applied once 5 days after the start of epidermal differentiation using a light‐emitting diode array with a center wavelength of 440, 523, 658 or 823 nm at a constant light intensity of 15 mW cm −2 for 50 or 600 s. Two days after PBM, we assessed the viability of the tissues by a water‐soluble tetrazolium‐8 assay, adenosine triphosphate measurements and live/dead cell imaging, and the results showed that the PBM at 823 nm for 50 s (0.75 J cm −2 ) significantly improved the viability of the 3D‐cultured skin. Abstract : Three‐dimensional (3D) cultured skin containing vascular networks is a useful skin substitute for transplantation. During its cultivation, however, insufficient nutrient delivery to the thick culture from the surrounding culture medium decreases tissue viability. To solve this problem, in this study, we applied photobiomodulation (PBM), which can optically activate the electron transport chain of mitochondria, to human 3D skin cultures. The effects of PBM were examined at four different center wavelengths: 440, 523, 658 and 823 nm. We found that PBM at 823 nm with the medium total light doses significantly improved the viability of the cultures.